Penerapan Permainan Jaring Hip Hop terhadap Hasil Belajar Sepak Sila - Ardian Firda; Mochamad Ridwan (Journal on Education, 2024)
This study aims to analyze the effect of the application of the Hip Hop Net game on the learning outcomes of football techniques in students. Sepak sila is a basic technique in the game of sepak takraw that requires skill, coordination, and precision. The method used in this study was a quasi design, involving 76 students as a sample, consisting of 37 students from class XI 1 and 39 students from class XI 3. The sample was selected based on demographic criteria and population size according to Hera & Elvandari (2021) and divided into two groups: an experimental group that gained learning with a Hip Hop Net game, and a control group that used conventional methods. The results of the study show that the game of Hip Hop Neting is more effective in improving football skills than conventional methods. This is shown by the average N-Gain value in the experimental class which reached 69.04% (medium category), with the highest N-Gain value of 100% (high category). In contrast, the control class showed an average N-Gain value of 43.9% (medium category), with the highest N-Gain value of 71.43%. These findings indicate that innovative learning approaches such as Hip Hop Netting games can make a positive contribution to improving students' sports skills. Therefore, it is recommended that the game of Neting Hip Hop be integrated into the physical education curriculum to improve the quality of learning and skills of students.